Analysis of The Impact of Change in Palm Oil’s Price on The Welfare of Farmers - Rizkia Zahra; Muhammad Yafiz (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Analysis of the Impact of Changes in Palm Oil Prices on the Welfare of Independent Smallholders. This study aims to analyze the impact of changes in oil palm prices on the welfare of farmers. The benefit of this research is to know the extent of the influence of changes in oil palm prices on the welfare of farmers, besides that farmers are more observant in caring for and reducing expenses in caring for oil palm land so that agricultural productivity and oil palm prices are in line with farmers' expectations. The research method used in this study is quantitative with the questionnaire method. The data analysis technique used is multiple linear analysis with the help of SPSS software. The results of this study indicate that changes in FFB prices on farmers' welfare can be seen that the effect of changes in oil palm prices is 0.778. The significance value for the effect of changes in FFB prices on farmers' welfare is 0.06 > 0.05 and the t-count value is 9.253 > t-table 2.02439.